Retail design - Mesher, Lynne. 4 0 16; 5 (Lausanne, Switzerland : AVA Pub., 2010)
Explores the interior design principles of retail space, discussing the relationship between interior and its context, site, and setting and featuring examples and diagrams.
Branding and identity -- What is branding? -- Developing a brand -- Selling the brand -- Retail sectors -- Food -- Fashion -- Home -- Leisure and entertainment -- Retail sites -- Department stores -- High street -- Shopping centres -- Out-of-town shopping -- The concourse -- Alternative venues -- The retail environment -- Retail and sustainability -- Materials -- Lighting -- Climate and sound -- -- Methods of organising space -- Principles of retail organisation -- Merchandising -- Service and ancillary space -- Design detail -- The shop façade -- Interior architecture -- Fixtures and fittings.
Includes bibliographical references (p. 170).
Adult;Adult
Keywords: 2 -- 0; 6; Stores, Retail.;Store decoration.;Stores.;Interior design; 20; 2